2014
DOI: 10.5539/jas.v6n4p1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis Between Antioxidant Activity and Phytochemicals in Korean Colored Corns Using Principal Component Analysis

Abstract: The colored corns are used as food as well as for feed in Asian countries; however, the active component of antioxidant activity in Korean colored corns has not been investigated. Thus, we measured the total content of carotenoids, phenols, flavonoids, and anthocyanins from 40 Korean colored corn genotypes for correlation analysis between antioxidant activity and these phytochemicals. The ferric reducing ability power (FRAP) and 2,2'-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…). Similar results were also seen in other studies . Our results showed that Flor del Rio is the only distinctly different accession.…”
Section: Resultssupporting
confidence: 93%
“…). Similar results were also seen in other studies . Our results showed that Flor del Rio is the only distinctly different accession.…”
Section: Resultssupporting
confidence: 93%
“…Just like DPPH, this result associated with TPC as FRAP assay showed significant correlation with TPC. This result is in agreement with other studies that discovered positive significant correlation between TPC and FRAP assay (Gan et al ., ; Ku et al ., ; Hanis Mastura et al ., ). Study by Kabouche et al .…”
Section: Discussionmentioning
confidence: 98%
“…These variations of correlation with antioxidant contents and assays may happen due to the variation of mechanism of action, delocalization of electron, solubility and redox potential. 27,62 FRAP can measure the activity of hydrophilic antioxidants, ABTS can measure both hydrophilic and lipophilic antioxidants, and DPPH can react only with those antioxidants that are soluble in organic solvents. 2,4,6 The evaluation of antioxidant capacity of these extracts with different assay methods has made the results more reliable since it has been shown that a single method of evaluating antioxidant activity may not be sufficient as no one method will be able to fully evaluate the antioxidant property of a given sample.…”
Section: Discussionmentioning
confidence: 99%